High-Throughput Electrospinning of Unmodified and Aminated Poly(Pentafluorostyrene) for Fiber-Reinforced Proton Exchange Membranes - Mu'min, Muhammad Solihul; Krieger, Anja; Wagner, Maximilian; Thiele, Simon; Kerres, Jochen (Macromolecular Materials and Engineering, 2025)
This study demonstrates a high-throughput fabrication of fiber interlayers for proton exchange membranes based on poly(pentafluorostyrene) (PPFSt) and its aminated derivatives. The fibers are produced by electrospinning, where the parameters are carefully screened. The controlled parameters are solvent composition, weight percentage, voltage, flow rate, and temperature, controlled with a self-designed heating jacket. The parameters are iterated toward optimized fiber structure and maximum output. The yielded fibers are infiltrated with Nafion and sulfonated polymer from bisphenol AF and decafluorobiphenyl (SFS001) by spray-coating and doctor blading to obtain the fiber-reinforced proton exchange membranes. Tensile tests reveal a higher Young's modulus and yield stress than pure Nafion. Here, the basicity of the aminated PPFSt fibers correlates with the Young's modulus due to improved acid-base interactions between amine groups and sulfonic acid. The acid-base interactions influence the composite membrane's proton conductivity, varying from 23 mS cm−1 for strongly alkaline fibers to 69 mS cm−1 for non-basic fibers. These findings can be transferred to fabricating fiber reinforcements beyond routinely used poly(benzimidazoles).
CRIS-Team Scopus Importer:2025-01-31
Keywords: composite membrane; electrospinning; nanofibers; polymer functionalization; proton exchange membrane